PROFESI AKUNTAN PEMERINTAH DI ‘ZAMAN NOW’: MASIHKAH MENARIK? - Isamah, Tezza Abdu; Wibowo, Puji (Indonesian Journal of Accounting and Governance, 2019)
Student perceptions towards accountant profession have been extensively discussed in manyliteratures. Along with an increase of central government financial reporting’s (LKPP) quality inIndonesia, bureaucratic sectors, on the other hand, are suffering from the lack of accountants. Thisresearch aims to investigate how regular students and civil servant students in Polytechnic of StateFinance STAN (PKN STAN) perceive the government accountant profession. By using conveniencesampling method, we found 208 respondents who answered our questionnaire adequately. This studysuggests both groups agree that government accountants are still needed to support national budgetaccountability. Regular students are relatively motivated to be government accountants than officerstudents. Unexperienced students are better-off in knowledge about government accountants, whilecivil servant students have stronger motivation to permanently work in government sector than regularstudents. Staff placement policy in Line Ministries/Agencies to accommodate PKN STAN graduatesbecomes an interesting policy implication in upcoming years.